2021
DOI: 10.1111/cdev.13632
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ethnic‐Racial Identity Developmental Processes on Global Bicultural Competence Development

Abstract: This study investigated ethnic-racial identity (ERI) developmental processes (i.e., exploration and resolution) as pathways for adolescents to develop global bicultural competence, or the ability to meet heritage and host cultural demands. The sample included 749 U.S. Mexican-origin youth (30% Mexico-born; 51% male) followed from early-to-late adolescence (M age = 12.79-17.38 years). Longitudinal structural equation analyses revealed that youth's sequential engagement in ERI exploration and resolution (from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…Focusing on bicultural facility and comfort is important because these behavioral (facility) and affective (comfort) components are theorized to be at the core of the development of the skills needed to navigate bicultural demands (Basilio et al, 2014). Importantly, prior work has suggested that the same processes may inform the development of behavioral and affective components of bicultural competence (Safa et al, 2021); thus, considering their joint development overtime may more accurately reflect bicultural youth's lived experiences in which they are concurrently relying upon skills to respond to bicultural demands behaviorally and affectively.…”
Section: Bicultural Competence Development: An Interplay Of Individua...mentioning
confidence: 99%
“…Focusing on bicultural facility and comfort is important because these behavioral (facility) and affective (comfort) components are theorized to be at the core of the development of the skills needed to navigate bicultural demands (Basilio et al, 2014). Importantly, prior work has suggested that the same processes may inform the development of behavioral and affective components of bicultural competence (Safa et al, 2021); thus, considering their joint development overtime may more accurately reflect bicultural youth's lived experiences in which they are concurrently relying upon skills to respond to bicultural demands behaviorally and affectively.…”
Section: Bicultural Competence Development: An Interplay Of Individua...mentioning
confidence: 99%
“…For example, bicultural emerging adults may look to their peers for cues about functioning effectively in the mainstream culture, perhaps seeing them as providing information more relevant to their current context (Wang et al, 2015(Wang et al, , 2019. This process may begin prior to college, particularly as the tasks of adolescence may speed up the psychological separation process by offering more opportunities for youth to engage with others outside of their immediate family environment (Arnett, 2007;Safa et al, 2021). Considering that our sample also reflected a higher average length of resettlement, in which a majority reported having arrived in the United States as adolescents, it is plausible that the circumstances of Burmese refugee students' resettlement may have enabled them to internalize the norms and practices of the This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that premigration stressors such as forced displacement, sociopolitical conflict, and religious persecution may impact the postresettlement experiences of Burmese refugees, but this research has tended to yield broader inferences about the adaptation of the Burmese refugee population as a whole instead of more nuanced individual differences (Lee et al, 2015). Making sense of one's relationship to culture and race/ ethnicity is a central developmental task during adolescence and emerging adulthood, particularly among ethnic-racial minority and bicultural youth (Safa et al, 2021;Umaña-Taylor et al, 2014). For Burmese refugees, the process of bicultural identity development may possibly be complicated by their resettlement experiences and the dynamic ecological processes that exert an influence on their evolving sense of self.…”
mentioning
confidence: 99%
“…Bicultural facility and comfort reflect components that emerged in focus groups with bicultural individuals (Basilio et al, 2014). These components are often correlated with one another (Carlo et al, 2016) and seem to be promoted by similar mechanisms (Safa et al, 2021). Individuals, however, may experience high levels of bicultural facility (e.g., have high levels of bicultural skills) and simultaneously low bicultural comfort (e.g., feel uncomfortable using bicultural skills) or vice versa.…”
Section: Bicultural Competence Developmentmentioning
confidence: 99%
“…However, no study, to our knowledge, has traced the separate but simultaneous development of bicultural facility and comfort as youths progress through college. Prior work has hinted at a cascade effect whereby the development of one of the bicultural competence components promotes the development of the other components (Safa et al, 2021). Particularly, the changing contexts and dynamic social environments encountered as youths progress through college may necessitate a renegotiation of one’s bicultural competencies to adapt to new demands and affordances, navigate increasing autonomy, and reconcile expectations of success at the school and family levels.…”
Section: Bicultural Competence Developmentmentioning
confidence: 99%